Association Studies in Advanced Breeding and Germplasm Lines of Chickpea (Cicer arietinum L.) - Soumith, Gundlapalli; Yasin, M.; Yadav, Rajendra; Sonaniya, Pallavi; Kumar, Sandeep; Khaleel, Mahvash (International Journal of Bio-resource and Stress Management, 2026)
The present investigation was conducted during rabi (October, 2021– April, 2022) in the research area of AICRP Chickpea, RAK College of Agriculture, Sehore, Madya Pradesh, India to study correlation analysis and path analysis for yield and its attributes among the 120 advanced breeding lines of chickpea. These lines derived from Desi×Desi, Desi×Kabuli, Kabuli×Desi and Kabuli×Kabuli crosses, as well as existing germplasm and varieties. The observations were recorded for eleven yield and its contributing traits. The correlation studies revealed that the traits such as plant height, leaflet size, biological yield, 100-seed weight and harvest index were found to be significantly associated with seed yield. Path analysis showed that biological yield plant-1 had highest direct effect towards the seed yield plant-1 followed by the harvest index, days to maturity, 100-seed weight, leaflet size, number of seeds pod-1, peduncle length indicating that selection of these traits would help in improving the seed yield plant-1 directly. Based on overall study of association analysis seven traits like leaflet size, plant height, peduncle length, seed yield plant-1, biological yield plant-1, 100-seed weight and harvest index were found to be determining characters for the improvement of yield in chickpea.